Application of lean Six Sigma to improve the dense medium separation performance at a diamond processing plant in Namibia. Issue 1 (31st December 2023) - Kanyemba, Abisai; Dzinomwa, Godfrey; Sony, Michael
Abstract: Lean Six Sigma (LSS) is a rigorous, data-driven, and results-oriented process improvement philosophy. To date, there is no evidence of a study of the application of LSS in a diamond plant. One of the most common recovery methods in the diamond industry has been dense medium separation (DMS), also known as heavy medium separation (HMS). The main purpose of the study is to investigate how to implement LSS to improve the dense medium separation performance at a diamond plant. Further, we investigate the factors impacting DMS by finding the most relevant factor/s and applying the principles of Lean and Six Sigma to improve the performance of dense medium separation (DMS) at a diamond plant in Namibia. The research found out that factors affecting DMS include cyclone pressure, medium density, viscosity, and worn cyclone parts and maintaining these parameters within narrow limits in relation to the correct set points is beneficial. Also, the study established that, operational conditions (cyclone pressures and medium densities) are the topmost factors affecting DMS followed by viscosity and lastly, equipment dimensions. The application of LSS reduced downtime delays and boosted the associated production, thus achieving cost-efficiency, improved DMS performance and reducing waste. Diamond mines are found in large numbers in Africa, and this study will help the mines to improve their efficiency. Further, using the lens of theory of swift and even flow, the LSS is applied in the diamond company to streamline the DMS performance. Further, it poses key implications for future LSS research.